Silozi, a mixed language: an analysis of the noun class system and kinship terms - Mbeha, Gustav Nyambe (Linguistics, 2018)
Silozi, the language of the Malozi people in Zambia and Namibia is a mixed language that has been the subject of a classification debate between scholars. Doke (1943) classifies Silozi in the same zone as Sesotho languages due to linguistic similarities. Guthrie (1948) in contrast, classify it independently because of its geographic location. Therefore, this study analyses and describes the mixed character of Silozi with focus on two areas. Firstly, the noun class system of Silozi is compared to those of Sesotho and the neighbouring languages to identify the origins of Silozi's noun classes. Secondly, present-day Silozi kinship terms are compared to Sesotho terms to determine which kinship terms are borrowed from Sesotho and which are not. The Silozi terms collected by early scholars are also compared with the presentday terms to identify differences. First hand language data was collected in the Kavuyu village (Zambia) and the Mahohoma settlement (Namibia) by employing a mixed methods approach. This involved the use of tailormade questionnaires which included open-ended questions and a wordlist. Furthermore, participant observations and open interviews were conducted. Twelve participants between the ages of 15 and 56 completed the questionnaire. Additionally, one family from each of the research sites was observed and for natural language data. The data used for comparative analysis was drawn primarily from Stirke and Thomas (1916) and Jalla (1936). Sesotho and Setswana native speakers were consulted for translations into the respective languages. The data analysis led to the following conclusions. Sesotho, Siluyana and some of the neighbouring languages contributed to Silozi significantly. The noun classes 1-10, 14 and 15 of Silozi are shared with Sesotho but the use has been modified due to contact with Siluyana. The diminutive classes 12-13 and locative classes 16-18 which have been lost in Sesotho were reinvented in Silozi through borrowing from Setswana and Siluyana. Most of Silozi's kinship terms from Sesotho have retained their semantic meanings but some have undergone semantic expansion. The kinship terms of non-Sesotho origin were borrowed from Siluyana and Simbunda. Though Silozi has more noun classes than its parent languages, it contains fewer kinship terms. The aim of this study is to illustrate the mixed character of Silozi in the noun class system and the kinship term, thus aiding the better understanding of Silozi.